ANALISA KUALITAS PELAYANAN PASIEN DI IGD RUMAH SAKIT GIGI DAN MULUT “X” SURABAYA - Nurullaily Kartika; Reny Natasya (Politeknik Ubaya, 2020)
Although service industries are invisible compared to manufacture, the global economy becomes more service oriented. The main characteristic of service feature is their production and sales occur simultaneously. It is quite difficult to measure service performance. However, the service quality of hospital service is considered to be an important topic of service management. IGD Dental and Medical service “X” in Surabaya is one of the hospital which provides Dental and Oral health in particular. This paper aims to identify the importance and performance of “X” Dental and Oral hospital which two methods (SERVQUAL and IPA) are able to explain significant amount of service quality.At the same time, the service quality factors of IPA model had more comprehensive consideration in comparison to SERVQUAL. SERVQUAL has five dimensions named Tangible, Reliability, Responsiveness, Assurance, and Emphaty . The research involving 70 participants. and the result is several dimensions of Importance Performance Analysis were proposed to improve service quality.Performance Analysis is important to improve the quality of services, such as by providing more complete and sophisticated medical facilities and equipment.